Peningkatan Kualitas Pembinaan Pranikah di Balai RW 5 Kelurahan Morokrembangan Kota Surabaya - Rohani Septya Triningsih; Rizkya Dwijayanti (Pusat Riset dan Inovasi Nasional, 2023)
This research examines how to improve the quality of premarital coaching in the RW 5 hall, Morokrembangan subdistrict, Surabaya city. Coaching is efforts, actions and activities carried out effectively and successfully to achieve better results. In general, coaching is considered a planned lifestyle improvement. Everyone has certain goals in life and wants to achieve these goals. If this life goal is not achieved, then people will try to rearrange their lifestyle. Premarital coaching is a knowledge and skills-based training program that providesand information related to marriage. Like how to maintain and maintain the integrity of the family. The research method used is descriptive qualitative to understand and explain the meaning behind reality. The aim of this research was to measure the effectiveness of improving the quality of premarital coaching in the RW 5 hall, Morokrembangan subdistrict, Surabaya city.